Implementation of a proactive referral tool for child healthcare professionals to encourage and facilitate parental smoking cessation in the Netherlands: a mixed-methods study - Tessa Scheffers-van Schayck; Bethany Hipple Walters; Roy Otten; Marloes Kleinjan (BMC, 2021)
Abstract Background Recently, the parent-tailored telephone based smoking cessation counseling program 'Smoke-free Parents' was shown to be effective in helping parents to quit smoking. To implement this program in child healthcare settings in the Netherlands, the research team developed a proactive referral tool to refer parents to Smoke-free Parents. The aim of the present implementation study was to explore the facilitators, barriers, and suggestions for improvement in the implementation of this referral tool. Methods Child healthcare professionals (N = 68) were recruited via multiple strategies (e.g., social media, mailings, and word of mouth among healthcare professionals) and invited to complete two online (quantitative and qualitative) questionnaires and to participate in a telephone semi-structured qualitative interview between April 2017 and February 2019. In total, 65 child healthcare professionals were included in the analyses. After inductive coding, thematic analyses were performed on the qualitative data. Descriptive analyses were performed on the quantitative data. Results The data from both questionnaires and the telephone interview revealed that the majority of the child healthcare professionals (92.3 % female; average years of working as a healthcare professional: 23.0) found the Smoke-free Parents referral tool accessible and convenient to use. Yet there were several barriers that limited their use of the tool. The data revealed that one of the main barriers that healthcare professionals experienced was parental resistance to smoking cessation assistance. In addition, healthcare professionals noted that they experienced tension when motivating parents to quit smoking, as they were not the parent's, but the child's healthcare provider. Additionally, healthcare professionals reported being concerned about the lack of information about the costs of Smoke-free Parents, which limited professionals referring parents to the service. Conclusions Although healthcare professionals reported rather positive experiences with the Smoke-free Parents referral tool, the use of the tool was limited due to barriers. To increase the impact of the Smoke-free Parents telephone-based smoking cessation counseling program via child healthcare settings, it is important to overcome these barriers. Suggestions for improvement in the implementation of the referral tool in child healthcare settings are discussed.